Materials of symposium and summer school “Fundamental Principles of Cancer Biotherapy”, May 21–23, 2018, Kyiv, Ukraine (Experimental Oncology, 2018)
The International Scientific Symposium “Fundamental Principles of Cancer Biotherapy” was held on May 21–23, 2018 in Kyiv, Ukraine. It was organized by R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology (IEPOR) of the National Academy of Sciences of Ukraine (NASU). The symposium was supported by the VACTRAIN project (TWINNING on DNA-based Cancer Vaccines, No 692293) in the frame of the European Union’s Horizon 2020 Research and Innovation Program.